2003
DOI: 10.1038/nm915
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD25+ regulatory T cells preserve graft-versus-tumor activity while inhibiting graft-versus-host disease after bone marrow transplantation

Abstract: Mature donor T cells cause graft-versus-host disease (GVHD), but they are also the main mediators of the beneficial graft-versus-tumor (GVT) activity of allogeneic bone marrow transplantation. Suppression of GVHD with maintenance of GVT activity is a desirable outcome for clinical transplantation. We have previously shown that donor-derived CD4+CD25+ regulatory T cells inhibit lethal GVHD after allogeneic bone marrow transplantation across major histocompatibility complex (MHC) class I and II barriers in mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

44
945
0
9

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 1,171 publications
(998 citation statements)
references
References 39 publications
44
945
0
9
Order By: Relevance
“…2A and B). These data are in line with previous studies defining a protective role for nTreg in GVHD [1,16]. In marked contrast, we did not observe any protective effect in mice receiving iTreg ( Fig.…”
Section: Resultssupporting
confidence: 94%
“…2A and B). These data are in line with previous studies defining a protective role for nTreg in GVHD [1,16]. In marked contrast, we did not observe any protective effect in mice receiving iTreg ( Fig.…”
Section: Resultssupporting
confidence: 94%
“…80 In mouse BMT models, naturally occurring donor-derived Tregs suppress the proliferation of conventional T cells, prevent GVHD and preserve GVL effects depending on the ratio of effector T cells to Tregs. [81][82][83][84][85][86] Furthermore, viral immunity is preserved in the presence of Tregs after allogeneic HCT. 87 The mechanisms for suppression in the context of GVHD remain completely unknown.…”
Section: Sensors Of Gvhdmentioning
confidence: 99%
“…Several studies have tried to solve this dilemma. It has been shown that CD4 + Treg from the donor or recipient can control GVHD after BM transplantation [21,[55][56][57][58]. In previous studies, we have found that donor DN-Treg could suppress donor CD8 + T cells, which caused GVHD in a single MHC-mismatched model [32].…”
mentioning
confidence: 90%